2020
DOI: 10.2147/ijn.s272736
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antibacterial Activity of Chitosan Nanoparticles Against Pathogenic N. gonorrhoea</p>

Abstract: The emergence of Neisseria gonorrhoeae strains that are resistant to the most commonly used antibiotics represents a great concern for global public health. This challenges the effectiveness of clinical treatment regimens and demands the development of alternative antigonococcal agent. In this regard, chitosan nanoparticles (CNPs) are known to have antimicrobial activity against a wide range of pathogens. Thus, they have become a potential candidate for combatting this era of multi-drug resistance. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…The gap of discovering new alternatives with regards to the emerging existing resistance to clinically prescribed antibiotics can be overcome by smart scientific exploitation and application of these chitosan properties. The antibacterial activity of chitosan NPs was examined against all strains of N. gonorrhea , including those resistant to multiple antibiotics, the results indicated chitosan NPs to inhibit growth with minimum inhibitory concentration of 0.16 to 0.31 mg/mL and a minimum bactericidal concentration of 0.31 to 0.61 mg/mL and no significant cytotoxicity [ 11 , 12 ].…”
Section: Properties Of Chitosanmentioning
confidence: 99%
“…The gap of discovering new alternatives with regards to the emerging existing resistance to clinically prescribed antibiotics can be overcome by smart scientific exploitation and application of these chitosan properties. The antibacterial activity of chitosan NPs was examined against all strains of N. gonorrhea , including those resistant to multiple antibiotics, the results indicated chitosan NPs to inhibit growth with minimum inhibitory concentration of 0.16 to 0.31 mg/mL and a minimum bactericidal concentration of 0.31 to 0.61 mg/mL and no significant cytotoxicity [ 11 , 12 ].…”
Section: Properties Of Chitosanmentioning
confidence: 99%
“…Chitosan nanoparticles (CNPs) also possess antimicrobial activity against a wide range of pathogens. CNPs are prepared by ionic gelation of different concentrations [ 116 ]. CNPs loaded with ampicillin, penicillin or diclofenac sodium show increased antibacterial properties [ 117 ].…”
Section: Nanotechnologymentioning
confidence: 99%
“…Most studies have been focused on the treatment of N. gonorrhoeae infection. In this sense, Ag NPs plus ceftriaxone [ 205 ], mercaptonitrobenzoic acid-coated Ag nanoclusters [ 206 ], and chitosan NPs [ 207 ] showed a great anti-gonococcal effect with minimal cytotoxicity. It has been also reported that PDGFR-β siRNA-PEI-PLGA-PEG NP significantly reduced the intracellular C. trachomatis concentration and bacterial extracellular release from infected cells more than 65% for both of them, while augmenting autophagic degradation and reducing bacterial binding in vitro [ 208 ].…”
Section: Nanoparticles and Human Infectionsmentioning
confidence: 99%